2017
DOI: 10.3390/met7100435
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Analysis and Electrochemical Behavior of Fe-Based Coating Produced by Laser Cladding

Abstract: Abstract:The effect of laser cladding on the surface microstructure and corrosion properties of coated/uncoated specimens were investigated. Fe-based alloy coating was produced on 35CrMo steel by laser cladding. The phase composition, microstructure, interface element distribution, microhardness and corrosion resistance of the cladding coating were measured. The results show that the cladding layer is mainly composed of α-Fe phases, the microstructure presents a gradient distribution, and a good metallurgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The work conducted by Zhong et al [13] showed that the formation of a Stellite-F alloy cladding layer on the surface of 316L stainless steel could improve its corrosion resistance. In addition, other works on the surface modification of other stainless steels (e.g., an Fe-based cladding layer on the surface of 35CrMo steel [14]) have shown that laser cladding enhances their corrosion and wear resistance [15][16][17]. Meanwhile, research regarding the effects of rare earth element alloying on the mechanical properties of materials has been performed.…”
Section: Introductionmentioning
confidence: 99%
“…The work conducted by Zhong et al [13] showed that the formation of a Stellite-F alloy cladding layer on the surface of 316L stainless steel could improve its corrosion resistance. In addition, other works on the surface modification of other stainless steels (e.g., an Fe-based cladding layer on the surface of 35CrMo steel [14]) have shown that laser cladding enhances their corrosion and wear resistance [15][16][17]. Meanwhile, research regarding the effects of rare earth element alloying on the mechanical properties of materials has been performed.…”
Section: Introductionmentioning
confidence: 99%
“…They proved that the post-treatment leads to martensite decomposition into finer tempered martensite with precipitations of numerous nano-sized Fe 3 C carbides [32]. Chen et al investigated the laser cladding of Fe-based coatings on rotating shafts made of 35CrMo steel, working in the seawater environment [33]. They successfully produced high-quality coatings characterized by high hardness and better corrosion resistance compared with the base metal of the substrate [33].Another interesting example of manufacturing a high performance Fe-based coating is the study conducted by Li et al [34], which was an investigation of the effect of carbon fibers addition to Fe-based coatings produced by laser cladding.…”
mentioning
confidence: 99%
“…Chen et al investigated the laser cladding of Fe-based coatings on rotating shafts made of 35CrMo steel, working in the seawater environment [33]. They successfully produced high-quality coatings characterized by high hardness and better corrosion resistance compared with the base metal of the substrate [33].Another interesting example of manufacturing a high performance Fe-based coating is the study conducted by Li et al [34], which was an investigation of the effect of carbon fibers addition to Fe-based coatings produced by laser cladding. They demonstrated a significant increase in the microhardness and wear resistance of the composite coatings containing also nano-size carbides [34].Hou et al investigated the influence of scanning speed during the laser cladding of Fe-based amorphous coatings on the microstructure and properties of coatings [35].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The thin, cladded coating can effectively reduce the cost of anti-wear materials [6,7]. Moreover, the cladded coating has a very limited influence on the matrix by creating a so-called heat-affected zone (HAZ) [8,9]. Different from other coating preparation techniques, such as physical vapor deposition or chemical vapor deposition, laser-cladded coating exhibits reliable metallurgical bonding between the coating and the matrix [10].…”
Section: Introductionmentioning
confidence: 99%